Research on Simulation Modeling of Dual Clutch Automatic Transmission for Real Time System - Li Zhanqi; Liu Quanzhou; Rong Hui (Jixie chuandong)
With the requirements of hardware-in-the-loop（ HIL） test of dual clutch Automatic transmission（ DCT） control unit（ TCU）,the real time simulation model of DCT is built based on Matlab/Simulink,mainly containing shift fork position,clutch torque,transmission torque and speed synchronization calculation modules,etc. The functional fault model module is developed on the basis of the real time model to realize the simulation of mechanical failures. The built DCT model is integrated into the whole vehicle model,a closed loop is constituted with real TCU,and the DCT model is validated online. The built model can be effectively used for the function and fail-safe testing of DCT-TCU.